Real convergence, price level convergence and inflation in Europe - Balázs Égert (Bruegel, 2007)
This paper provides a comprehensive review of the factors that can cause price levels to diverge and which are at the root of different inflation rates in Europe including the EU-27. Among others, we study the structural and cyclical factors influencing market and nonmarket-based service, house and goods prices, and we summarise some stylised facts emerging from descriptive statistics. Subsequently, we set out the possible mismatches between price level convergence and inflation rates. Having described in detail the underlying economic factors, we proceed to demonstrate the relative importance of these factors on observed inflation rates first in an accounting framework and then by relying on panel estimations.
Keywords: E43; E50; E52; C22; G21; O52; 330; price level; inflation; Balassa-Samuelson; tradables; house prices; regulated prices; Europe; transition; Preisniveau; Inflation; Balassa-Samuelson Effekt; EU-Staaten